Faktor-Faktor Yang Mempengaruhi Firm Value Sebelum Dan Di Masa Covid-19 - Jessica Lavena, Yanti (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
The purpose of this study is to examine the variables that affect firm value as well as to examine the differences in firm value before and during the COVID-19 period. The research methods used are multiple linear regression analysis and different test with IBM SPSS. The sampling technique used is purposive sampling which resulted in 47 manufacturing companies listed on the IDX. The results of the regression test before the COVID-19 period showed that profitability and dividend policy have an effect on firm value, while liquidity, leverage and firm size have no effect on firm value. The results of the regression test during the COVID-19 period showed that profitability has an effect on firm value, while liquidity, leverage, firm size and dividend policy have no effect on firm value. The result of the different test showed that there is no difference in the average of firm value before and during the COVID-19 period.